(untitled) (Research, Society and Development, 2021)
Maxillofacial trauma is a public health problem, requiring large investments in the area. Epidemiology varies in the literature, in degree, type, etiology, socioeconomic and cultural factors. They can have aesthetic, functional and psychological consequences for when dead. Multidisciplinary planning and management of complex cases is important for clinical success. The objective of this work is to present a clinical case of the multidisciplinary treatment of a patient victim of a motorcycle accident, referred to the Integrated Clinic of the Dentistry course at the Tiradentes University Center (UNIT-AL), which involved the following areas: oral surgery, endodontics, restorative dentistry, periodontics and oral rehabilitation. The interconnection of the areas of Dentistry was essential for the success of the clinical case.